The Annulment of the Constitutional Court's Decision from the Perspective of Hans Kelsen's Pure Legal Theory (Validity & Applicability of Norms) - Hidayah, Rahmad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The phenomenon of the annulment or delegitimization of Constitutional Court (MK) decisions raises significant legal and theoretical issues in Indonesia’s legal system, given that such decisions are constitutionally final and binding. This study aims to analyze the possibility of invalidating MK decisions through the lens of Hans Kelsen’s Pure Theory of Law, focusing on the concepts of norm validity and applicability within the legal system’s hierarchical structure. The research applies a normative juridical approach, using deductive and interpretative analysis of primary and secondary legal materials, alongside the Grundnorm theory to assess the position of MK decisions within the norm structure. The findings reveal that although formally derived from a constitutional institution, the validity of MK decisions may still be questioned if they are inconsistent with the fundamental norms of the Constitution. The absence of a formal mechanism to revoke MK decisions creates tension between legal positivism and substantive justice. The study concludes that Kelsen’s theory offers a robust conceptual framework for objectively evaluating legal norms and provides a philosophical basis for reforming oversight mechanisms against judicial deviation. Thus, this research contributes to the advancement of normative-positivist legal theory discourse and encourages the renewal of understanding regarding the legitimacy of constitutional adjudication in Indonesia.